2018
DOI: 10.1016/j.amepre.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Financial Incentives and Mailing Nicotine Patches to Help Medicaid Smokers Quit Smoking: A Cost–Benefit Analysis

Abstract: An RCT designed to increase Medicaid smokers' quitting success was conducted in California during 2012−2013. In the trial, alternative cessation treatment strategies were embedded in the state's ongoing quitline services. It found that modest financial incentives of up to $60 per participant and sending nicotine patches induced significantly higher cessation rates compared with usual care alone and usual care plus nicotine patches. Building upon that study, this study assessed potential population-level costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…There have been various interventions targeting tobacco use and food insecurity among the low-income population 10. For example, California implemented the Medi-Cal Incentives to Quit Smoking programme (known as MIQS) in 2011–2015 to provide incentives to Medi-Cal smokers to call the California Smokers Helpline 4849.…”
Section: Discussionmentioning
confidence: 99%
“…There have been various interventions targeting tobacco use and food insecurity among the low-income population 10. For example, California implemented the Medi-Cal Incentives to Quit Smoking programme (known as MIQS) in 2011–2015 to provide incentives to Medi-Cal smokers to call the California Smokers Helpline 4849.…”
Section: Discussionmentioning
confidence: 99%
“…26 The final MIQS article compares the costs and benefits of these three CSH cessation interventions. Sung et al 27 found that the Arm 3 intervention yielded the greatest cost savings. Compared with the Arm 1 (i.e., telephone counseling only) group, the Arm 3 group would save additional healthcare costs with a benefit−cost ratio of 1.90 over a 10-year period.…”
Section: Effectiveness Of Incentivizing Quitting Behaviorsmentioning
confidence: 99%
“…However, the benefits of quitting smoking expressed in QALYs were estimated using a Markov model, and the authors estimated incremental costs of £482 (€541) per QALY . Another study that performed a cost–benefit analysis for a large cohort of Medicaid enrollees found that providing quitline callers with modest financial incentives was a cost‐effective method to increase cessation rates over a 10‐year horizon with a benefit–cost ratio of 1.30 .…”
Section: Introductionmentioning
confidence: 99%